Oxygen Plasma Modified Carbon Cloth with C=O Zincophilic Sites as a Stable Host for Zinc Metal Anodes - Jiang, Baozheng; Liu, Wenbao; Ren, Zhilong; Guo, Rongsheng; Huang, Yongfeng; Xu, Chengjun; Kang, Feiyu (Frontiers in Chemistry, 2022)
Aqueous zinc-ion batteries (ZIBs) are currently receiving widespread attention due to their merits of environmental-friendly properties, high safety, and low cost. However, the absence of stable zinc metal anodes severely restricts their potential applications. In this work, we demonstrate a simple oxygen plasma treatment method to modify the surface state of carbon cloth to construct an ideal substrate for zinc deposition to solve the dendrite growth problem of zinc anodes. The plasma treated carbon cloth (PTCC) electrode has lower nucleation overpotential and uniformly distributed C=O zincophilic nucleation sites, facilitating the uniform nucleation and subsequent homogeneous deposition of zinc. Benefiting from the superior properties of PTCC substrate, the enhanced zinc anodes demonstrate low voltage hysteresis (about 25 mV) and stable zinc plating/stripping behaviors (over 530 h lifespan) at 0.5 mA cm−2 with 15% depth of discharge (DOD). Besides, an extended cycling lifespan of 480 h can also be achieved at very high DOD of 60%. The potential application of the enhanced zinc anode is also confirmed in Zn|V10O24·12H2O full cell. The cells with Zn@PTCC electrode demonstrate remarkable rate capability and excellent cycling stability (95.0% capacity retention after 500 cycles).